Do Ensino da Arquitectura à arquitectura do Ensino - Ana Marta Neves e Silva (2021)
Considering architecture simultaneously as an expression and in"uence in the construction of the world, societies and life, it is essential to clarify both in which world one builds and which world is intended to (re)build. #us, designing in architecture subtly becomes designing through architecture. To provoke a future, anticipating it through the constructions in the present, leads us to consider that it will be the children of the present to inhabit that future. As in Architecture, we see in Education the same capacity to raise circumstances. Despite being one of the greatest foundations of any paradigm or transformation, the truth is that this power has been neglected. Educational spaces continue to respond to ideologies whose genesis took place almost two centuries ago and need therefore an urgent revision. Combining the capacity of both - Architecture and Pedagogy -, besides the need for a pedagogical review, it is also necessary to renew the character of school spaces so that they welcome, enable or instigate renewed approaches. #us, rethinking what the school is as an ideological-space makes us rethink about what this school may be as a physical-space so that they build each other mutually and contribute to a common goal - the construction of a school in and for the 21st century. Given that it suggests as mottos some aspects that were considered throughout an interdisciplinary questioning, the competition Unschool Copenhagen, Rede!ne Learning arises as an opportunity to rehearse a projectual translation of some themes of encounter between the two disciplines.